Judicial Specialization and the Adjudication of Immigration Cases - Baum, Lawrence (2010)
When scholars and policymakers consider proposals for specialized courts, they are usually and appropriately mindful of the potential effects of specialization on the adjudication of cases. Focusing on the immigration field, this Article considers these potential effects in relation to other attributes of adjudication: the difficulty of cases, the severe caseload pressures, and the strong hierarchical controls that are each important attributes at some or all levels of the adjudication system. Specifically, this Article discusses the effects of those attributes, the effects of judicial specialization, and the intertwining of the two. It applies that analysis to proposals to substitute some type of specialized court for the federal courts of appeals in the adjudication of immigration cases. The Article concludes that the impact of adopting such a proposal could be substantial but that it is also quite uncertain. To a considerable degree, the impact depends on the form of specialization adopted and on other provisions of the legislation that creates a specialized court